PENDAMPINGAN DALAM PENYUSUNAN LAPORAN KEUANGAN MASJID AL-IKHLAS DENGAN PENERAPAN APLIKASI EXCEL - Santoso, Setiyo Hadi; Windasari, Ihsanul (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The management of community donation funds must be accountable and transparent. The main problem faced by the mosque administrators is the limited time available to complete financial report administration. The manual financial recording used by the mosque administrators does not optimize the available functions. As a result, the data entry process takes longer and is prone to human error. This community service program involves interviews, observations, discussions, and practical training for preparing mosque financial reports using Microsoft Excel formulas and functions. Regarding financial reporting for non-profit entities, it is expected that the administrators of Al-Ikhlas Mosque will be able to create financial reports that are accountable to the community members who donate part of their wealth to the mosque. The evaluation indicates that this program has successfully enhanced the understanding and skills required for preparing mosque financial reports. These reports can now be held accountable to the community and be easily understood by interested parties.